King-Devick test normative reference values and internal consistency in youth football and soccer athletes - Moran, R. N.; Covassin, T. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The King-Devick (K-D) test has gained popularity as a sideline concussion assessment tool, comprising of visual tracking and saccadic eye movements. However, limited normative data exists for youth athletes under the age of 13. The purpose of this study was to establish normative reference values and examine the internal consistency of the K-D test in youth athletes. The K-D test was administered to 422 youth football and soccer athletes prior to their respective season. The average K-D score was 54.29±11.5 seconds. Across the two trials, 55% of participants committed at least one error. Overall, the K-D test demonstrated a high internal consistency (Cronbach a = 0.92) when administered at baseline. Inter-item correlations revealed a moderate to strong relationship between test cards and trials (r range= 0.71 to 0.95; p<0.001), along with test cards and baseline K-D time (r range= 0.85 to 0.94; p<0.001). Although the K-D test was consistent during baseline testing, the high percentage of errors at baseline makes the K-D test questionable for post-concussion comparisons.